Phytosociololgical studies on the vegetation of sand dunes and sandy plains of ajmer (Rajasthan) - Sharma, Beena; Sharma, Kavita (Current Botany, 2011)
The phytosociololgical study of Ajmer sand dunes shows that three sites of the study i.e. Leela Sewri, Pushakr Valley Base & Pachkund, are dominated by Acacia senegal (Mimosaceae). Acacia tortilis (Mimosaceae) and Eucalyptus camaldulensis (Myrtaceae). All these three species are represented by highest frequency values in class-A. Species such as Acacia leucophloea, Acacia senegal, Acacia tortilis and Maytenus emarginata are present in all three localities and are different in respect of phytosociololgical parameters, height, girth and canopy width. In the present study shrubs and trees of sand dunes were differentiated on the basis of profile diagrams and scattering patterns of height and canopy width.Â